Diagnosis and Management of Hematological Adverse Events Induced by Immune Checkpoint Inhibitors: A Systematic Review - Omar, Nabil E.; El-Fass, Kareem A.; Abushouk, Abdelrahman I.; Elbaghdady, Noha; Barakat, Abd Elmonem M.; Noreldin, Ahmed E.; Johar, Dina; Yassin, Mohamed; Hamad, Anas; Elazzazy, Shereen; Dermime, Said (Frontiers in Immunology, 2020)
There has been less volume of literature focusing on the Immune-related Hematological Adverse Drug Events (Hem-irAEs) of Immune Checkpoint Inhibitors (ICPis) in cancer patients. Furthermore, there has been no consensus about the management of hemato-toxicity from immunotherapy in the recently published practice guidelines by the European Society for Medical Oncology ESMO. We conducted a systematic review of case reports/series to describe diagnosis and management of potentially rare and unrecognized Hem-irAEs. We searched Google scholar, Embase, Medline, OVID, Web of Science and ScienceDirect for eligible articles. Data were extracted on patient characteristics, Hem-irAEs, and management strategies. We performed quality assessment using the Pierson-5 evaluation scheme and causality assessment using the Naranjo scale. Our search retrieved 49 articles that described 118 cases. The majority of patients had melanoma (57.6%) and lung cancer (26.3%). The most common Hem-irAEs reported with ICPis (such as nivolumab, ipilimumab, and pembrolizumab) were thrombocytopenia, hemolytic and aplastic anemias. Less reported adverse events included agranulocytosis and neutropenia. Steroids were commonly used to treat these adverse events with frequent success. Other used strategies included IVIG, rituximab and transfusion of blood components. The findings of this review provide more insights into the rarely reported irAEs of ICPis.